Edukasi Kepada Masyarakat Daun Pegagan Berkhasiat Sebagai Pelembab Wajah - Monica Suryani; Suharyanisa Suharyanisa; Ferdinand Paulus Ginting; Syarifah Roslianizar; Widya Fitri (FKIP, Universitas Palangka Raya, 2024)
Gotu kola leaves have active compounds in the form of alkaloids, flavonoids, saponins, and tannins, which are secondary metabolites. A sheet mask is a more practical facial care cosmetic preparation without rinsing, effectively moisturizing facial skin. This service aims to provide education to the public about the benefits of gotu kola leaves as a natural facial moisturizer. This community service activity is carried out using an outreach method to the community individually using material presentations using power points and print media in Langkat. The results of implementing this educational activity have increased the insight and knowledge of the participants, especially children, teenagers, and mothers, in the form of using clove leaves as a herbal plant to overcome hair growth problems. The results of the participants' knowledge level from the pre-test and post-test scores are in the good category. Previously, people did not know the benefits of gotu kola leaves, which are efficacious as a natural facial moisturizer; now people can use them.